Cubic Perovskite Fluoride as Open Framework Cathode for Na‐Ion Batteries. (29th May 2017) - Cao, Dunping; Yin, Congling; Shi, Dingren; Fu, Zhengwen; Zhang, Jincang; Li, Chilin
Abstract : Exploring novel structure prototype and mineral phase, especially open framework material, is crucial to developing high‐performance Na‐ion battery cathodes in view of potentially faster intrinsic diffusion of Na + in lattices. Perovskite phases have been widely applied in solar cells, fuel cells, and electrocatalysis; however, they are rarely attempted as energy storage electrode materials. This study proposes pre‐expanding perovskite iron fluoride (KFeF3 ) framework by stuffing large‐sized K + as a channel filler, which is advantageous over Na +, NH4 +, and H2 O molecule filler in terms of structure robustness, symmetry, and connectivity. K + stuffing leads to the preservation of a more "regular" cubic phase with fast isotropic 3D diffusion as a consequence of no distortion of FeF6 octahedra during K‐Na electrochemical exchange and following Na‐insertion cycling. High‐rate Na‐storage is achievable with a reversible capacity of 110, 70, and 40 mAh g −1 at 0.1, 2, and 10 C, respectively, for this open framework fluoride cathode, benefiting from solid solution electrochemical behavior and high intrinsic diffusion coefficient. It is thought that this rate performance is currently the best among Na‐storage fluoride materials. Abstract : Pervoskite iron fluoride (KFeF3 ) of open framework is proposed as a high‐rate Na‐ion battery cathode. Prestuffing large‐sized K + into channels leads to the preservation of cubic phase with fast isotropic 3D diffusion as a consequence of no distortion of FeF6 octahedra during first K‐extraction and following Na‐storage cycling.